+0  
 
0
227
1
avatar+644 

 

Enter (A,B,C) in order below if A, B, and C are the coefficients of the partial fractions expansion of \(\frac{2(x^2+x-1)}{x(x^2-1)} = \frac{A}{x} + \frac{B}{x-1} + \frac{C}{x+1}.\)
 

waffles  Mar 9, 2018
 #1
avatar+20013 
0

Enter (A,B,C) in order below if A, B, and C are the coefficients of the partial fractions expansion of 

\(\displaystyle \frac{2(x^2+x-1)}{x(x^2-1)} = \frac{A}{x} + \frac{B}{x-1} + \frac{C}{x+1}. \)
 \frac{2(x^2+x-1)}{x(x^2-1)} = \frac{A}{x} + \frac{B}{x-1} + \frac{C}{x+1}.

 

 

\(\small{ \begin{array}{|rcll|} \hline \dfrac{2(x^2+x-1)}{x(x^2-1)} &=& \dfrac{2(x^2+x-1)}{x(x-1)(x+1)} \\ \\ \hline \\ \dfrac{2(x^2+x-1)}{x(x-1)(x+1)} &=& \dfrac{A}{x} + \dfrac{B}{(x-1)} + \dfrac{C}{(x+1)} \qquad | \qquad \cdot x(x-1)(x+1) \\\\ 2(x^2+x-1) &=& \dfrac{A\cdot x(x-1)(x+1)}{x} + \dfrac{B\cdot x(x-1)(x+1)}{(x-1)} + \dfrac{C\cdot x(x-1)(x+1)}{(x+1)} \\\\ && \boxed{ 2(x^2+x-1) = A (x-1)(x+1) + B x (x+1) + C x(x-1) } \\\\ \hline \end{array} }\)

 

\(\small{ \begin{array}{lcll} \hline \mathbf{x = 0:} & 2(0+0-1) &=& A (0-1)(0+1) + B \cdot 0 (0+1) + C \cdot 0 (0-1) \\ & -2 &=& -A \\ & \mathbf{A} &\mathbf{=}& \mathbf{2} \\ \\ \hline \mathbf{x = 1:} & 2(1+1-1) &=& A (1-1)(1+1) + B\cdot 1 (1+1) + C \cdot 1(1-1) \\ & 2 &=& A \cdot 0(1+1) + B\cdot 1 (1+1) + C \cdot 1\cdot 0 \\ & 2 &=& 2B \\ & \mathbf{B} &\mathbf{=}& \mathbf{1} \\ \\ \hline \mathbf{x = -1:} & 2(1-1-1) &=& A (-1-1)(-1+1) + B\cdot (-1) (-1+1) + C \cdot (-1)(-1-1) \\ & -2 &=& A (-1-1)\cdot 0 + B\cdot (-1) \cdot 0 + C \cdot (-1)(-1-1) \\ & - 2 &=& 2C \\ & \mathbf{C} &\mathbf{=}& \mathbf{-1} \\ \hline \end{array} }\)

 

\(\mathbf{(A,B,C) = (2,1,-1)}\)

 

laugh

heureka  Mar 9, 2018

35 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.